2018
DOI: 10.1145/3233524
|View full text |Cite
|
Sign up to set email alerts
|

Packing Groups of Items into Multiple Knapsacks

Abstract: We consider a natural generalization of the classical multiple knapsack problem in which instead of packing single items we are packing groups of items. In this problem, we have multiple knapsacks and a set of items which are partitioned into groups. Each item has an individual weight, while the profit is associated with groups rather than items. The profit of a group can be attained if and only if every item of this group is packed. Such a general model finds applications in various practical problems, e.g., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
(15 reference statements)
0
9
0
Order By: Relevance
“…This paper studies GMKP, a strongly N P-hard problem with no polynomial time approximation algorithm. We are not the first studying GMKP [Chen and Zhang, 2018], but we are the first studying the bi-criteria version of GMKP and offering a broad computational study of our suggested algorithms and heuristics. We propose several pseudo-polynomial time approximation algorithms for bi-GMKP with tight guarantees, that can be adapted as binary-search heuristics for GMKP, and heuristics for bi-GMKP.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This paper studies GMKP, a strongly N P-hard problem with no polynomial time approximation algorithm. We are not the first studying GMKP [Chen and Zhang, 2018], but we are the first studying the bi-criteria version of GMKP and offering a broad computational study of our suggested algorithms and heuristics. We propose several pseudo-polynomial time approximation algorithms for bi-GMKP with tight guarantees, that can be adapted as binary-search heuristics for GMKP, and heuristics for bi-GMKP.…”
Section: Discussionmentioning
confidence: 99%
“…There is a PTAS, but not an FPTAS for MKP; even for two knapsacks [Chekuri and Khanna, 2005]. There is no PTAS nor constant-ratio approximation algorithm for GMKP [Chen and Zhang, 2018].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chen and Zhang [11] studied the problem of group packing of items into multiple knapsacks (GMKP), a special case of Group GAP where the profit of each item is the same across the XX:2 Generalized Assignment via Submodular Optimization bins. Let GMKP(δ) be the restriction of GMPK to instances in which the total size of items in each group is at most δm (that is, a factor δ of the total capacity of all bins).…”
Section: Prior Workmentioning
confidence: 99%